Don't forget to write for the elementary grades : 50 enthralling and effective writing lessons ages 5 to 12 - Traig, Jennifer; 826 National (Organization) (San Francisco : Jossey-Bass, 2011)
If you believe that teaching creative writing should be done creatively, you've picked up the right book. Don't Forget to Write for the Elementary Grades offers elementary teachers 50 creative writing lesson plans developed by the imaginative and highly acclaimed 826 National writing centers. The book is designed to be a handy teacher's aide that can help reach and inspire all students ages 5 to 12 (even those most resistant to creative writing). The lesson range from silly ("Brains! or Writing with Zombies") to practical ("How to write a How To"), from sports to science, music to mysteries, and everything in between (yes, there is an academic purpose to having Harry Potter and Spiderman battle some evil ninjas). Each lesson is written by educators, 826 volunteers, celebrated authors, actors, and writers, and all are linked to rigorous writing standards. (cover verso).
Lesson plans: -- Tragic love tales (by 6 year-olds) -- Writing for pets -- Fort party! -- Make-believe science -- Oh, you shouldn't have, really ... -- Space exploration for beginners: what to do when you meet an alien -- Magic realism -- Recycled elves: fairy tale do-overs -- Creating a guide to modern girlhood -- How to write a how-to -- Talking trash! -- Why did the chicken cross the lesson plan? Writing jokes and riddles -- Spy school -- Literary mash-ups -- Brain spelunking -- PJ party -- Any which way: choosing your own adventure -- Life-size board game! -- Brains! Or, writing with zombies -- How to write a comic -- The meaning of life (the short answer): Writing big, large, and small! -- How to survive anything -- Vindicated villains -- Ono-mato-what-now? -- All-star sports stories -- I wrote a guidebook and all I got was this lousy t-shirt: travel writing -- Cooking for cryptids: the definitive cryptozoological cookbook -- Science club: ice cream! -- Sticky words -- Maddening mad libs -- If I were a king or queen: creating your own country -- How to be a detective -- Harry Potter Spider-Man vs. The evil zombie ninjas! -- Out there: drawing and writing new worlds: an interdisciplinary art and writing lesson -- Whining effectiely: or, how to persuade your parents -- For the birds! -- There's poetry in an atom: writing creatively about science -- Guerrilla poetry -- Fankenfilms -- The rules of magic -- And now I will perform an interpretive dance: kinetic writing -- Note to self: writing autobiography -- Smell this story, taste this poem -- Grammarama: homonym stand-off -- How to be the next President of the United States! Or, how to write a really, really, really good letter -- Character assassination! -- Sonnets with superpowers -- Best imaginary vacation ever! -- What's the scoop? How to get the real story -- The illustrated book report.
Keywords: English language -- Composition and exercises -- Study and teaching (Elementary) -- United States; Education, Elementary -- Activity programs -- United States